Multilateral Trade Cooperation: What Next? - Hoekman, B; Vines, D (2007)
This paper first briefly describes the role of the WTO and its history. It then lays out a simple bargaining model of international negotiations, which can be used for understanding the Doha round of talks. This simple framework is used to distil and discuss a number of potential explanations for the difficulties that have arisen in concluding these talks, as well as a number of systemic questions that confront WTO members. A key question is whether the WTO should concentrate primarily on market access or on further expanding its coverage to deal with regulatory issues or with other domestic policies that may have an impact on trade. Given the difficulties that arise in agreeing on 'behind the border' disciplines, we argue that a continued focus on market access and enforcement of market access commitments is likely to prove most fruitful.